Pengaruh IPM, Tingkat Pengangguran dan Pertumbuhan Ekonomi Terhadap Kemiskinan Di Jawa Timur - Muhammad Handy Rakhmawan; Tony Seno Aji (Jurnal Ekonomika : INDEPENDEN, 2022)
Poverty is a social problem that is global in nature and hinders the welfare of human civilization, poverty is a complex and unending problem that has long been felt by people in developing countries, including Indonesia. This study aims to see how the HDI, unemployment rate and economic growth affect poverty in the Regencies/cities of East Java Province in 2020. Quantitative approach is the type of method used in this study by using secondary data cross section of 38 regencies/cities in East Java Province and using the classical multiple linear regression assumption test to analyze the data. The results showed that partially the HDI variable had a significant negative effect on poverty, while the unemployment rate and economic growth variables had a positive but not significant effect. However, simultaneously the variables HDI, unemployment rate and economic growth have a simultaneous effect on poverty.